2020
DOI: 10.3390/jcm9082514
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Solitary Pulmonary Nodules Based on Virtual Monochrome Images and Iodine-Dependent Images Using a Single-Source Dual-Energy CT with Fast kVp Switching

Abstract: With lung cancer being the most common malignancy diagnosed worldwide, lung nodule assessment has proved to be one of big challenges of modern medicine. The aim of this study was to examine the usefulness of Dual Energy Computed Tomography (DECT) in solitary pulmonary nodule (SPN) assessment. Between January 2017 and June 2018; 65 patients (42 males and 23 females) underwent DECT scans in the late arterial phase (AP) and venous phase (VP). We concluded that imaging at an energy level of 65 keV was the most acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…The best discrimination capability was found for the Model combination rather than the Model AP and Model VP , yielding an AUC of 0.8772 (95% CI 0.780–0.974). A recent study [ 30 ] showed that imaging at an energy level of 65 keV yielded the best diagnostic accuracy in identifying malignant solitary pulmonary nodules on AP and VP monochromatic images, with AUCs of 0.855 and 0.858, respectively. Compared with this study, the combination radiomics model (AUC of 0.8772) may show better performance at an energy level of 70 keV.…”
Section: Discussionmentioning
confidence: 99%
“…The best discrimination capability was found for the Model combination rather than the Model AP and Model VP , yielding an AUC of 0.8772 (95% CI 0.780–0.974). A recent study [ 30 ] showed that imaging at an energy level of 65 keV yielded the best diagnostic accuracy in identifying malignant solitary pulmonary nodules on AP and VP monochromatic images, with AUCs of 0.855 and 0.858, respectively. Compared with this study, the combination radiomics model (AUC of 0.8772) may show better performance at an energy level of 70 keV.…”
Section: Discussionmentioning
confidence: 99%
“…The DECT modality displays the accumulation of a contrast agent measured in conventional CT in HU units as its concentration in 1 cm 3 of tissue, which is a unique solution. In pulmonary diagnostics it is used to assess malignancy of lung tumors 26,27 or to differentiate the subtypes of malignant tumors 28 , assess lung vessels [29][30][31] and lung tissue pathologies 32,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Also, as iodine images indicate the vascularity of pulmonary nodules, they contribute to their characterization (Fig. 14 ) [ 24 ].
Fig.
…”
Section: Materials Decompositionmentioning
confidence: 99%